2008
DOI: 10.1089/end.2007.0269
|View full text |Cite
|
Sign up to set email alerts
|

Tubeless Percutaneous Nephrolithotomy: Is it Really Less Morbid?

Abstract: Significantly less pain, lower analgesia requirement, and shorter hospital stay with early return to normal activities were observed in the tubeless PCNL group v the primary nephrostomy tube PCNL group. Tubeless PCNL in selected patients is a secure, effective, and less morbid procedure that does not compromise patient safety and concerns. We recommend that tubeless PCNL be the preferred procedure in selected patients for management of nephrolithiasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
61
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 24 publications
7
61
0
1
Order By: Relevance
“…12 Several studies since then have demonstrated that tubeless and totally tubeless PCNL have equivalent outcomes in the properly selected patient group when compared to PCNL performed with the presence of a nephrostomy tube (with/without stent). 2,3,5,6,10,11 Our study also demonstrated that totally tubeless PCNL have equivalent outcomes in the properly selected patients. In our study perioperative blood loss, transfusion, and the complication rate in the totally tubeless group were comparable to the standard group.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…12 Several studies since then have demonstrated that tubeless and totally tubeless PCNL have equivalent outcomes in the properly selected patient group when compared to PCNL performed with the presence of a nephrostomy tube (with/without stent). 2,3,5,6,10,11 Our study also demonstrated that totally tubeless PCNL have equivalent outcomes in the properly selected patients. In our study perioperative blood loss, transfusion, and the complication rate in the totally tubeless group were comparable to the standard group.…”
Section: Discussionsupporting
confidence: 51%
“…Despite this, tubeless PCNL retains its role in selected patients with renal stones who are undergoing uncomplicated PCNL. 3,6,[21][22][23] However, a nephrostomy tube should be placed if serious disruption or significant laceration of the collecting system is noted. Also, if significant intrarenal bleeding is found and endoscopic visualization is impossible, a nephrostomy tube should be inserted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since this report, several other investigators have confirmed that tubeless PCNL leads to shorter hospital stays and less postoperative pain (16,18,19) and decreased cost as compared to nephrostomy tube drainage (7,20). While most studies have utilized a ureteral stent in patients undergoing a tubeless PCNL, other investigators have recommended a "totally tubeless" approach (21,22).…”
Section: Discussionmentioning
confidence: 88%
“…blood transfusion, emergency nephrostomy, significant bleeding needing intervention or worse stone clearance rates (Table 3). [6][7][8][9][10][11][12][13] Agrawal et al 7 conducted a randomised comparison of 101 'tubeless' PCNLs (Group B; with JJ stent) with 101 standard PCNLs (Group A; with nephrostomy). All patients had an 'uneventful' postoperative recovery.…”
Section: Discussionmentioning
confidence: 99%